Determination of vitamins K1 , MK-4, and MK-7 in human serum of postmenopausal women by HPLC with fluorescence detection - Klapkova, Eva; Cepova, Jana; Dunovska, Katerina; Prusa, Richard (Journal of clinical laboratory analysis, 2018)
BACKGROUND: New high-performance liquid chromatography (HPLC) method was developed for the determination of vitamin K1 and two forms of vitamin K2 (MK-4 and MK-7) in human serum, and the levels of vitamin K were determined in 350 samples of postmenopausal women. METHODS: Vitamin K was determined by HPLC with fluorescence detection after postcolumn zinc reduction. The detection was performed at 246 nm (excitation) and 430 nm (emission). The internal standard and 2 mL of ethanol were added to 500 μL of serum. The mixture was extracted with 4 mL of hexane, and solid phase extraction was then used. RESULTS: The HLPC method was fully validated. The intra- and interday accuracy and precision were evaluated on two QC samples by multiple analysis, and CV were less than 10%. The limit of quantification for MK-4 was found at 0.04 ng/mL, for K1 0.03 ng/mL, and for MK-7 0.03 ng/mL. The mean recoveries of the corresponding compounds were 98%-110%. Serum levels of MK-4, K1 , and MK-7 in postmenopausal women with osteoporosis were 0.890 ± 0.291 ng/mL, 0.433 ± 0.394 ng/mL, and 1.002 ± 1.020 ng/mL, respectively (mean ± SD). Serum levels of MK-4, K1 , and MK-7 in postmenopausal women without osteoporosis were 0.825 ± 0.266 ng/mL, 0.493 ± 0.399 ng/mL, and 1.186 ± 1.076 ng/mL, respectively (mean ± SD). CONCLUSION: New HPLC method for the determination of vitamins K1 , MK-4, and MK-7 in serum was evaluated and validated. This method is highly specific and sensitive with the low limit of quantification.
Keywords: Vitamin K 1; menaquinones; Chromatography, High Pressure Liquid; Humans; vitamin K; vitamin K 1; Female; phylloquinone; lidé; vitamin K 2; postmenopauza; MK-7; Fluorescence; časové faktory; Postmenopause; ženské pohlaví; MK-4; HPLC; Vitamin K 2; fluorescence; Time Factors; vysokoúčinná kapalinová chromatografie